Acute Hemiparesis in a Healthy Elderly Woman: Where and What Is the Lesion? - Lee, Ji Hoon; Heo, Sung Hyuk; Lee, Jin San; Chang, Dae-Il; Park, Ki-Ho; Sung, Ji-Youn; Hong, Il Ki; Kim, Myeong Hee; Park, Bong Jin; Choi, Woo Suk (Frontiers in Neurology, 2017)
Hemiparesis may be the result of lesions in the contralateral pyramidal tract in the brain or, less frequently, in the ipsilateral pyramidal tract in the upper cervical spinal cord. However, although rare, multiple lesions that simultaneously occur in both of these regions may be the cause of acute hemiparesis, and the clinical symptoms can often be misdiagnosed as a stroke. In addition, the correct diagnosis of these multiple central nervous system (CNS) lesions is very challenging if they are caused by infection from an unexpected microorganism. We evaluated an elderly healthy woman who presented with acute hemiparesis and multiple brain and spinal cord lesions that were confirmed to occur from an infection with Propionibacterium acnes (P. acnes). In this report, the differential diagnosis and histopathological findings are discussed for these multiple CNS lesions in this healthy woman.